2022
DOI: 10.56093/ijas.v92i12.104323
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter partitioning in Bt and non Bt cotton (Gossypium hirsutum) cultivars under different sowing environments of Punjab

Abstract: A field experiment was conducted at Punjab Agricultural University (PAU), Regional Research Station (RRS), Faridkot and Bathinda during rainy (kharif) season 2017 to evaluate the performance of Bt and non Bt cotton (Gossypium hirsutum L.) cultivars under different sowing environments. The experiment was laid out in split plot design with 3 sowing dates (April 20, May 10 and May 30) in main plots and 4 American cotton cultivars [2 Bt cultivars (NCS 855 BGII and RCH 650 BGII) and 2 non Bt cultivars (F 2228 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Thus, from the above results, it can be inferred that early sown crop stays for longer time in the field to utilize optimum available temperature and solar radiation which leads to higher thermal units accumulation in line with Hebber et al (2002). Contrarily late sown crop pushes the reproductive phases to cooler environments which reduces the accumulation of heat units (Kaur et al, 2019;Sankaranarayanan et al, 2020). Among the studied cultivars, difference between Bt and non Bt cultivar was greater at early growth stages, which got narrowed with the advancement of crop growth stages.…”
Section: Accumulated Thermal Unitsmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, from the above results, it can be inferred that early sown crop stays for longer time in the field to utilize optimum available temperature and solar radiation which leads to higher thermal units accumulation in line with Hebber et al (2002). Contrarily late sown crop pushes the reproductive phases to cooler environments which reduces the accumulation of heat units (Kaur et al, 2019;Sankaranarayanan et al, 2020). Among the studied cultivars, difference between Bt and non Bt cultivar was greater at early growth stages, which got narrowed with the advancement of crop growth stages.…”
Section: Accumulated Thermal Unitsmentioning
confidence: 91%
“…Both, early and delayed sowings are harmful for crop growth and productivity. Nevertheless, too early sown cotton crop attains the longer vegetative phase (Kaur et al, 2022) but, experiences shorter reproductive time which further coincids with the period of warm temperature resulting in serious yield loss (Parlawar et al, 2018). On the other hand, delayed sowing leads the reproductive phase towards the cooler temperature, lower sunshine durations, reduced photosynthetic activity, lesser carbohydrate transition to sink structures and overlapping of the vegetative and reproductive phases with each other leading to poor yield (Kaur et al, 2019;Sankaranarayanan et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gwathmey and Clement, 2010;Kaur et al, 2022). Similarly, wider spacing of 90 x 15 cm increased the individual plant biomass.…”
mentioning
confidence: 88%
“…Ali et al [9] showed that 15 th April to 10 th May sown cotton gave maximum crop growth rate. Kaur et al [14] studied on three sowing dates (20 th April, 10 th May, and 30 th May) revealed that the crop growth rate (CGR) was greater for the cotton sown earlier 20 th April. The range from 90-120 DAS (days after sowing) produced the maximum RGR.…”
Section: Introductionmentioning
confidence: 99%